RP-HPLC-DAD를 이용한 발효 삼출건비탕의 생물전환 성분 분석 - 양혜진(Hye Jin Yang); 량춘(Chun Liang); 마진열(Jin Yeul Ma); 이광진(Kwang Jin Lee) (생약학회지, 2013)
Samchulgeonbi-tang (SC) is well-known traditional herbal medicine which is composed of fourteen medicine herbs. SC has been used for the treatment of the chronic gastritis, indigestion, gastric ulcers, gastroptosis and diarrhea disease. The variation in the amount of bioactive components of SC and its fermentation SC with ten Lactobacillus strains were investigated via high-performance liquid chromatography coupled with diode array detection (HPLC-DAD). Simultaneous qualitative and quantitative analysis of seven bioactive compounds; paeoniflorin, liquiritin, hesperidin, liquiritigenin, kaempferol, atractylenolide III, magnolol were achieved by comparing their retention times ($t_R$) and UV spectra with those of the standard compounds. In the results, the amount of paeoniflorin and hesperidin were 7.967 mg/g, 7.251 mg/g that were the main compounds in SC. The amounts of liquiritigenin was increased by all ten Lactobacillus strains, except strain 128. Especially, the liquiritigenin amount was highest in SC fermented with strain 145 (0.201 mg/g), which was increased by 158.39% compared to SC (0.081 mg/g). In the fermented SC using strains 344, almost components were increased than non-fermented SC, except paeoniflorin and kaempferol. Thus, these results considered that the strains 145 and 344 are most excellent fermentation strains among the 10 species of fermentation strains.